The Handbook of technology and second language teaching and learning - Chapelle, Carol A.; Sauro, Shannon 1973- (Hoboken, NJ Wiley Blackwell, 2017)
"This book presents a comprehensive exploration of the impact of technology on the field of second language learning"--Provided by publisher
From past to present: a hundred years of technology for L2 learning / Sue E. K. Otto -- Technologies for teaching and learning L2 grammar / Trude Heift and Nina Vyatkina -- Technologies for teaching and learning L2 vocabulary / Qing Ma -- Technologies for teaching and learning L2 reading / Meei-Ling Liaw and Kathryn English -- Technology and L2 writing / Zhi Li, Ahmet Dursun and Volker Hegelheimer -- Technologies for teaching and learning L2 listening / Philip Hubbard -- Technologies for teaching and learning L2 speaking / Robert J. Blake -- Technologies for teaching and learning intercultural competence and interlanguage pragmatics / Julie M. Sykes -- Distance language teaching with technology / Cynthia J. White -- Blended language learning: research and practice / Maja Grgurovi -- Telecollaboration / Melinda Dooly -- The continuing evolution of virtual worlds for language learning / Randall W. Sandler -- Digital gaming in L2 teaching and learning / Jonathon Reinhardt -- Mobile learning revolution: implications for language pedagogy / Agnes Kukulska-Hulme, Helen Lee and Lucy Norris -- Technology for task-based language teaching / Marta Gonzâalez-lloret -- Language for specific purposes and corpus-based pedagogy / Elena Cotos -- Technology, new literacies, and language learners / Paige Ware -- Language teacher education and technology / Greg Kessler and Philip Hubbard -- Integrating assessment with instruction through technology / Joan Jamieson and Matteo Musumeci -- Technology and high-stakes language testing / Jonathan E. Schmidgall and Donald E. Powers -- Validation of technology-assisted language tests / Yoo-Ree Chung -- Authoring language learning courseware / Robert Godwin-Jones -- Design-based research / Julio C. Rodrâiguez -- Evaluation of technology and language learning / Carol A. Chapelle -- Research methods for investigating technology for language and culture learning / Dorothy M. Chun -- Call meta-analyses and transparency analysis / Hsien-Chin Liou and Hui-Fen Lin -- Researching technology-mediated multimodal interaction / Thierry Chanier and Marie-Noelle lamy -- Technology enhanced SLA research / Bryan Smith -- Toward langua-technocultural competence / Shannon Sauro and Carol A. Chapelle
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching -- Technological innovations; Second language acquisition